2014
DOI: 10.1673/031.014.61
|View full text |Cite
|
Sign up to set email alerts
|

Biology, Temperature Thresholds, and Degree-Day Requirements for Development of the Cucumber Moth,Diaphania indica, under Laboratory Conditions

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…The caterpillar, Diaphania indica (Saunders) (Lepidoptera: Crambidae) is one of the major insect pests of T. anguina in India and Sri Lanka (Roopa et al ., 2014). The insect is also a serious pest of cucumber, melon, gherkin, bottle gourd, bitter gourd, snake gourd, luffa, little cucumber and cotton (Tripathi and Pandy, 1973; Pandey, 1977; Clavijo et al ., 1995; Hosseinzade et al ., 2014). The first to third-instar larvae feed on the lower surface of leaves, while fourth and fifth-instar larvae gregariously consume leaves.…”
Section: Introductionmentioning
confidence: 99%
“…The caterpillar, Diaphania indica (Saunders) (Lepidoptera: Crambidae) is one of the major insect pests of T. anguina in India and Sri Lanka (Roopa et al ., 2014). The insect is also a serious pest of cucumber, melon, gherkin, bottle gourd, bitter gourd, snake gourd, luffa, little cucumber and cotton (Tripathi and Pandy, 1973; Pandey, 1977; Clavijo et al ., 1995; Hosseinzade et al ., 2014). The first to third-instar larvae feed on the lower surface of leaves, while fourth and fifth-instar larvae gregariously consume leaves.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have focused on the effects of lighting on animal behavior and internal physiology and metabolism at the genetic and protein levels (Edery, 2000;Glaser and Stanewsky, 2005;Lohmann et al, 2007;Fuller et al, 2008). Insects are cold-blooded, thus temperature is directly involved in the regulation of physiological behavior mechanisms including hatching and feeding, growth and metamorphosis, reproduction and diapause, and migration and calling (Zhu et al, 2008a(Zhu et al, /2008bTanaka and Watari, 2011;Xu et al, 2012;Hosseinzade et al, 2014;Liao et al, 2014;Soltani Orang et al, 2014). A Drosophila study found that cyclical changes in temperature with differences of 2-3°C reset and synchronized the circadian clock (Gentile et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The pests include those affecting cucurbits worldwide as well as those which are more pronounced in certain regions of the globe, where they attain the status of primary pests. Cucumber moth, Diaphania indica , is a potentially damaging pest of cucurbitaceous vegetables worldwide ( Chintha et al, 2002 ; Kinjo and Arakaki, 2002 ; Hosseinzade et al, 2014 ; Dai et al, 2018 ; Jalali et al, 2019 ; Capinera, 2020 ; Debnath et al, 2020 ; Khanzada et al, 2021 ). The attractiveness of cucurbitaceous host plants for D. indica was observed to depend on the species and condition of the plant (uninfested and infested), and sex, mating status and experience of the insect.…”
Section: Biotic Stress Responses In Cucurbitsmentioning
confidence: 99%